2013
DOI: 10.1017/s1041610213001701
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity of the Center for Epidemiologic Studies Depression Scale short form in older population in China

Abstract: The CES-D 10 Scale indicated adequate reliability and validity for the community-dwelling older population in China. In addition, the data revealed that perception and expression of depressive feelings was different between male and female elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
195
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(200 citation statements)
references
References 26 publications
(65 reference statements)
4
195
0
1
Order By: Relevance
“…A review of the literature of published CES-D-10 validation studies revealed that except for one study with over 16,000 participants [20], sample sizes for one factor solution varied from as low as 47 to 755 [11,18,19,21,3539]. Also, two studies with sample sizes of 1013 and 742 reported a two factor solution [16,17]. Considering generally low factor loadings, and/or more than one latent variable in SEMs, this suggests that most published studies to date have been underpowered and at risk of inappropriate conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the literature of published CES-D-10 validation studies revealed that except for one study with over 16,000 participants [20], sample sizes for one factor solution varied from as low as 47 to 755 [11,18,19,21,3539]. Also, two studies with sample sizes of 1013 and 742 reported a two factor solution [16,17]. Considering generally low factor loadings, and/or more than one latent variable in SEMs, this suggests that most published studies to date have been underpowered and at risk of inappropriate conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The Andresen version, CES-D-10, has strong reliability and excellent sensitivity and specificity in screening for major depression in older adults [14]. Construct validity of the short form of the CES-D has been examined in Singaporean older adults in community settings [16], Chinese elderly in community dwelling [17] and older Chinese in social centres [18]. While the published validity studies of the CES-D-10 illustrated acceptable factorial validity there were indications that the factorial structure has not been consistently determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRS used an 8-item CES-D, while the CHARLS used a 10-item CES-D. Both scales have good internal consistency, test-retest reliability, factorial validity, and construct validity in China (Boey, 1999; Chen and Mui, 2014; Lei et al, 2014) and the U.S. (Steffick, 2000). The CES-D scales in the HRS and the CHARLS have six items in common, as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The above measurement scales have been used successfully in other studies with Chinese populations [16, 18, 21, 22]. In addition, HIV knowledge regarding transmission and prevention of HIV/AIDS was measured by 11 true/false/unsure questions.…”
Section: Methodsmentioning
confidence: 99%